2016
DOI: 10.3389/fcimb.2016.00143
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Phylogenetic Characterization of Non-O157 Shiga Toxin-Producing Escherichia coli Strains in China

Abstract: Shiga toxin-producing Escherichia coli (STEC) causes diarrhea and hemorrhagic colitis with life-threatening complications, such as hemolytic uremic syndrome. The aim of this study was to assess the molecular epidemiologic features of non-O157 STEC strains from different resources in China and illustrate the role of animal reservoirs or animal-derived foodstuffs in human STEC infections. A collection of 301 non-O157 STEC isolates from domestic and wild animals (i.e., cattle, goat, pig, yak, pika, and antelope),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
40
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 45 publications
8
40
1
Order By: Relevance
“…Raw beef had more non‐O157 STEC isolates compared to all other types of foodstuffs (45%) ( χ 2 , p < .1), that was expected given that bovines are the main environmental reservoir of various STEC serogroups, both O157 and non‐O157 serogroups (Karmali et al, ; Synge, ). Our findings agrees with reports obtained from India and the rest of the world indicating that foodstuffs of bovine origin were found to carry higher numbers of STEC, including non‐O157 serogroups (Bai et al, ; Hazarika et al, ; Manna et al, ; Sinha et al, ; Xia et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Raw beef had more non‐O157 STEC isolates compared to all other types of foodstuffs (45%) ( χ 2 , p < .1), that was expected given that bovines are the main environmental reservoir of various STEC serogroups, both O157 and non‐O157 serogroups (Karmali et al, ; Synge, ). Our findings agrees with reports obtained from India and the rest of the world indicating that foodstuffs of bovine origin were found to carry higher numbers of STEC, including non‐O157 serogroups (Bai et al, ; Hazarika et al, ; Manna et al, ; Sinha et al, ; Xia et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly raw fish isolates vt 1 (four isolates) and vt 2 (three isolates), notably none of the isolates was carrying both of vt 1 and vt 2 genes. Similar results of the carriage of vt 1 and vt 2 (or stx 1 and stx 2 genes) by non-O157 isolates from raw beef (Bai et al, 2016;Sinha et al, 2015;Xia et al, 2010), raw fish (Gupta et al, 2013), raw chicken (Momtaz & Jamshidi, 2013), raw milk (Neher et al, 2015), were reported around the world including Indian subcontinent, in all these reports, no unified association was found between the type of VT gene and the sources of isolates, for example, Sinha et al (2015) found that stx 2 genes were more prevalent in ground beef samples in India, while Bosilevac and Koohmaraie (2011) reported the predominance of stx 1 gene among the STEC isolates in ground beef in the United States. Similar to the results reported in this study, Joris, Pierard, and De Zutter (2011) reported that vt 1 and vt 2 genes were equally harbored by the 18 non-O157 STEC isolates from cattle at slaughter in Belgium.…”
Section: Diversity Of Stec Serogroups In Foodstuffs Of Animal Originsupporting
confidence: 59%
See 2 more Smart Citations
“…The O26 serogroup bearing the pathotype eae + stx 1 + highlighted in this study was isolated from a patient with HUS (Mora et al 2012) and patients with diarrhoea in China according to the data by Bai et al (2016).…”
Section: Isolation and Characterization Of Isolated Strainsmentioning
confidence: 99%